MENTAL HEALTH AND SOCIAL FUNCTIONING OF CHILDREN AND ADOLESCENTS WITH CELIAC DISEASE - Stojanovic-Jovanovic, Biljana; Jovanovic, Stevan; Vuletic, Biljana (HEALTH CARE, 2020)
Introduction/Aim: Celiac disease is a systemic autoimmune disease characterized by persistent gluten intolerance. The condition imposed by the disease, a special gluten-free diet, often causes stress, which in children, especially adolescents, can lead to disturbances in mental health and social functioning. The aim of the study is to examine whether there are significant differences between children and adolescents with celiac disease and their peers without celiac disease in relation to their mental health and social functioning.Methods: The study included 116 children and adolescents aged 5-18 years with a diagnosis of celiac disease and 116 children and adolescents without celiac disease. The study groups were matched by age and gender. In addition to the general questionnaire, the Screen for Child Anxiety Related Disorder (SCARED) was used to assess the level of anxiety. The chi-squared test was used in the statistical analysis of the data.Results: Subjects with and without celiac disease did not differ significantly in gender and age. Children and adolescents with celiac disease had significantly more frequent anxiety (33.9%) (p
Keywords: celiac disease, children, gluten, nutrition, mental health, social functioning